Effect of Vitamin D Level on Clinical Outcomes in Patients Undergoing Left Ventricular Assist Device Implantation. (30th March 2018) - Obeid, Fadi Abou; Yost, Gardner; Bhat, Geetha; Drever, Erin; Tatooles, Antone
Abstract: Background: Vitamin D is an important hormone that regulates cardiac myocyte function. Low levels contribute to the development of cardiovascular disease and have been implicated in immune function and the inflammatory cascade. Patients who undergo left ventricular assist device (LVAD) implantation are at risk for driveline infection, stroke, and gastrointestinal (GI) bleeding. We investigated whether serum 25‐hydroxy (25‐OH) vitamin D levels affect clinical outcomes after LVAD. Methods: 212 patients who underwent LVAD implantation between 2010 and 2015 were included. We measured preoperative 25‐OH vitamin D level and postoperative adverse events during the first year. Vitamin D level was classified into 3 categories: normal (>30 ng/mL), insufficient (20–30 ng/mL), and deficient (<20 ng/mL). Clinical outcomes in both insufficient and deficient categories were compared with the normal category. Results: The odds ratio (OR) of being admitted ≥2 times was 2.46 (95% confidence interval [CI]: 1.067–5.769) for deficiency and 2.5 (95% CI: 0.970–6.443) for insufficiency. The OR of driveline infection was 6.185 (95% CI: 0.80–49.2; P = .07) for insufficiency and 11.467 (95% CI: 1.204–109.26; P = .03) for deficiency. Vitamin D levels were not associated with GI bleeding, length of stay, or stroke. Conclusions: In patients with LVAD, both deficiency and insufficiency of 25‐OH vitamin D levels are independently associated with increased postoperative driveline infection risk and higher rate of readmission. Further trials are needed to confirm whether a repletion regimen could be a promising means of decreasing the risk for these postoperative adverse events.